ORIGIN OF THE OLYMPIC IDEA IN THE KINGDOM OF SERBIA AND ITS REALIZATION AT THE END OF 19th AND BEGINNING OF THE 20th CENTURY - Slađana Mijatović; Violeta Šiljak (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
Although the idea of revival of the Ancient Olympic Games had appeared in the works of the humanists starting from the 15th century, from Dover's Olympic games - Cotswold games (1604); Leopold Frederic's festivals similar to the Ancient Olympic Games (1772-1779); Olympic Games in the Greek village of Letrino (1930), Olympic Games of Ling's successors in Helsinki (1834-1836); Olympic festivities in Athens (1859, 1870, 1875, 1888 and 1889); Modern Olympic Games were resumed only in 1894 at the Sports Congress in Paris. The ideas on revival on the Olympic Games reached the Principality and Kingdom of Serbia in the second half of the 19th century. They were accepted and started to be realized in the area of Serbian sport. It is mentioned that a public lecture on the Olympic Games of Hellenes was held in 1860s in the Kasina inn in Belgrade. In the 1890s many private schools and civil gymnastic societies in Belgrade used the term Olympic competitions. Equestrian events in Cuprija, held in March 1896 were called Olympic festivities and the Knights society "Dusan Silni" announced its program of public class in which "for the first time would be performed the famous Olympic game with swards of the Hellenic times" in February 1896 before the first Olympic Games held in Athens (April 1896). Sreten Stojkovic in his book: "Physical education and its reforms" (1897) wrote that it was necessary to organize Serbian Olympic Festivities as well. At the beginning of the 20th century, a gymnastic society in Belgrade was named Serbian Olympia and Knights society "Dusan Silni" organized in Belgrade, together with Belgrade journalists, the Olympic Games (1908) at the river island Ada Ciganlija. In the high school of Jagodina, teachers and students established the Olympic club (1910), which organized Students' Olympic Games (1910). Finally, the Olympic idea was realized in the Kingdom of Serbia by establishment of the Serbian Olympic Club (committee) 1910 which was admitted to the International Olympic Committee (IOC) (1912) in Stockholm during the 5th Olympic Games, where two participants of the Kingdom of Serbia took part. Captain Svetomir Djukic then become and remained a member of the IOC till 1948.